Outcome of the First wwPDB/CCDC/D3R Ligand Validation Workshop - Adams, Paul D; Aertgeerts, Kathleen; Bauer, Cary; Bell, Jeffrey A; Berman, Helen M; Bhat, Talapady N; Blaney, Jeff M; Bolton, Evan; Bricogne, Gerard; Brown, David; Burley, Stephen K; Case, David A; et al. (Structure (London, England, 2016)
Crystallographic studies of ligands bound to biological macromolecules (proteins and nucleic acids) represent an important source of information concerning drug-target interactions, providing atomic level insights into the physical chemistry of complex formation between macromolecules and ligands. Of the more than 115,000 entries extant in the Protein Data Bank (PDB) archive, ∼75% include at least one non-polymeric ligand. Ligand geometrical and stereochemical quality, the suitability of ligand models for in silico drug discovery and design, and the goodness-of-fit of ligand models to electron-density maps vary widely across the archive. We describe the proceedings and conclusions from the first Worldwide PDB/Cambridge Crystallographic Data Center/Drug Design Data Resource (wwPDB/CCDC/D3R) Ligand Validation Workshop held at the Research Collaboratory for Structural Bioinformatics at Rutgers University on July 30-31, 2015. Experts in protein crystallography from academe and industry came together with non-profit and for-profit software providers for crystallography and with experts in computational chemistry and data archiving to discuss and make recommendations on best practices, as framed by a series of questions central to structural studies of macromolecule-ligand complexes. What data concerning bound ligands should be archived in the PDB? How should the ligands be best represented? How should structural models of macromolecule-ligand complexes be validated? What supplementary information should accompany publications of structural studies of biological macromolecules? Consensus recommendations on best practices developed in response to each of these questions are provided, together with some details regarding implementation. Important issues addressed but not resolved at the workshop are also enumerated.
Keywords: molekulární modely; směrnice jako téma; datové kurátorství; Crystallography, X-Ray; Guidelines as Topic; proteiny; Ligands; Models, Molecular; Proteins; Protein Conformation; krystalografie rentgenová; databáze proteinů; ligandy; konformace proteinů; Databases, Protein; Data Curation